OPPORTUNITIES AND CHALLENGES IN LANGUAGE EDUCATION IN THE AGE OF ARTIFICIAL INTELLIGENCE - Mishra, Badri Narayan; Shriprakash (International Journal of Research -GRANTHAALAYAH, 2025)
In the age of artificial intelligence, the nature of language education is rapidly changing. AI-based chatbots, translators, voice-recognition systems, and adaptive learning platforms are making the language learning process personalized, effective, and accessible. Students can practice at their own pace and improve their pronunciation, grammar, vocabulary, and writing skills. This has made language learning more engaging, accessible, and relevant. However, it also brings with it numerous challenges—such as excessive technological dependence, a decline in creativity, a crisis of linguistic authenticity, data security threats, and technological inequality. AI machines cannot fully understand human emotions, cultural contexts, and creative expression, so the human role in language education remains indispensable. Thus, while AI has enriched language education with new opportunities, the need for its balanced and judicious use is equally important.